HUBUNGAN PENYERAPAN AIR DENGAN KEKUATAN GESER PERLEKATAN BAHAN RELINER PERMANEN PADA BASIS GIGI TIRUAN RESIN AKRILIK - , Fei In; , Drg Endang Wahyuningtyas, MS, Sp Pros (K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Denture that has been used for long period time, reducing their fitting surface of the mucosal tissue. One of the treatments by relining procedure, namely adding a new resin material on the surface fitting denture base. Materials commonly used as reliner consisted of polymethylmethacrylate (PMMA) or acrylic resin. Denture base reliner material consisting of hard denture liner and soft liner. The purpose of this study was to determine the presence of water absorption relationship with the shear adhesion strength of the material permanently reliner, they are: cold cured acrylic resin, heat cured and a soft liner on denture base acrylic resin. This study consisted of thirty subjects of heat-cured acrylic resins base were treated the reliner with shape of cylindrical diameter of 4 mm, thickness 2 mm and divided into 3 groups. Group I, the surface of the acrylic resin base which treated with hard denture liner heat cured acrylic resin. Group II, the surface of the acrylic resin base which treated with hard denture liner cold cured acrylic resin. Group III, the surface of the acrylic resin base which treated with soft liner heat cured acrylic resin. The research subjects immersed for 1 week in distilled water, in 37Â°C and weighed. Shear strength tests performed by Universal Testing Machine-Pearson Panke. Research data were analyzed with correlation analysis and followed by analysis of covariance. The results of the Pearson correlation analysis showed that there was negative correlation between weights of water absorbed by cold cured permanent reliner, heat cured reliner, and the soft liner. The results of analysis of covariance (ANACOVA) showed that there was significant effect of differences of reliner material shear strength. (P < 0.05). Conclusion: there is a relationship between the absorption of water to shear strength of permanent cold cured reliner, heat cured, and soft liner, into denture base acrylic resin. Hard denture liner heat cured has the lowest water absorption, so its shear strength to denture base acrylic resin is the highest.